Biomarkers for trials of neuroprotection in Parkinson's disease. Issue 1 (24th August 2012) - Agarwal, Pankaj A.; Stoessl, A. Jon
<x xml:space="preserve">Abstract</x> With increased understanding of disease pathogenesis and the foreseeable reality of disease‐modifying therapies, there is a growing need to find biomarkers that will allow early (preferably preclinical) detection of disease and that will provide an independent readout of disease progression. In this article, we review a variety of markers, with a focus on functional imaging techniques, which while imperfect, currently provide the best approach to this problem. We consider the limitations of functional imaging of the dopamine system in assessing the progression of Parkinson's Disease (PD) as well as the potential use of structural imaging and emerging progress in other biochemical and molecular markers. While there is no single biomarker that will satisfy all requirements, some combination is likely to be of great use in identifying those subjects most likely to benefit from neuroprotective therapies, as well as in monitoring the effects of these interventions. © 2013 Movement Disorder Society